IMPLEMENTASI GOOD ENVIRONMENTAL GOVERNANCE DALAM PENGELOLAAN SAMPAH DI KOTA DEPOK TAHUN 2023: - Azzura, Davena Rasyafa; Mulyawan, Rahman; Saefulrahman, Iyep (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The issue of waste management in Depok City has become increasingly serious due to the growing population, intensified urban activities, and the limited capacity of the Cipayung Final Disposal Site (TPA), which has now exceeded its capacity. In 2023, the daily waste generation in Depok City reached 963.79 tons, a figure that is disproportionate to the available waste management capacity. The objective of the research is to determine how the Depok City Government implements the principles of Good Environmental Governance in waste management. This study employs a qualitative approach using descriptive analysis. Data collection techniques were conducted through primary and secondary sources. The results of the study indicate that the implementation of the principles of Good Environmental Governance has not been optimal. Although there is a sufficient regulatory framework through Regional Regulation Number 13 of 2018 and Mayor Regulation Number 65 of 2018, implementation in the field still faces various structural, cultural, and technical obstacles.